Threats to Poland’s sovereignty and international standing - Bernaciński, Łukasz; Janowski, Jacek; Krysiak, Zbigniew; Kwaśniewski, Jerzy; Szczucki, Krzysztof (A thousand years of Poland’s presence among the elite of European states, 2026)
The panel discussion addressed threats to Polish sovereignty, both external and internal. Participants agreed that the most serious external threat is the ongoing centralization of the European Union and the drive to create a European superstate that would strip member states of key competencies. Additional threats include the EU migration pact and plans to build a common European army that would compete with NATO. Professor Janowski placed these processes in a broader context, pointing to the so-called Great Reset — a global concentration of power, property, and information in the hands of supranational corporations and investment funds operating beyond the control of nation-states. Professor Krysiak drew on the thought of Robert Schuman, who as early as the 1960s warned against the federalist ideology of Altiero Spinelli, which serves as the intellectual foundation of the current EU reforms. In his view, reforming the EU from within is impossible — what is needed is an organized resistance movement on a pan-European scale. In the closing portion of the discussion, the panelists highlighted internal threats: the weakening of state institutions, the failure to reckon with the communist past, the excessive power of the judiciary, and the growing demoralization of society. Attorney Kwaśniewski emphasized that the destabilization of the Polish state may serve external interests — generating public demand for order imposed by an EU sovereign. At the same time, he expressed confidence that Poland, as the largest country capable of effectively resisting EU centralization, has a real chance of blocking that process.